Aging increases senescence, calcium signaling, and extracellular matrix deposition in human airway smooth muscle. - Sarah A Wicher (Public Library of Science (PLoS), 2021)
Lung function declines as people age and their lungs become stiffer. With an increasing elderly population, understanding mechanisms that contribute to these structural and functional changes in the aging lung is important. Part of the aging process is characterized by thicker, more fibrotic airways, and senile emphysema caused by changes in lung parenchyma. There is also senescence, which occurs throughout the body with aging. Here, using human airway smooth muscle (ASM) cells from patients in different age groups, we explored senescence pathways and changes in intracellular calcium signaling and extracellular matrix (ECM) deposition to elucidate potential mechanisms by which aging leads to thicker and stiffer lungs. Senescent markers p21, γH2AX, and β-gal, and some senescence-associated secretory proteins (SASP) increased with aging, as shown by staining and biochemical analyses. Agonist-induced intracellular Ca2+ responses, measured using fura-2 loaded cells and fluorescence imaging, increased with age. However, biochemical analysis showed that expression of the following markers decreased with age: M3 muscarinic receptor, TRPC3, Orai1, STIM1, SERCA2, MMP2 and MMP9. In contrast, collagen III, and fibronectin deposition increased with age. These data show that senescence increases in the aging airways that is associated with a stiffer but surprisingly greater intracellular calcium signaling as a marker for contractility. ASM senescence may enhance fibrosis in a feed forward loop promoting remodeling and altered calcium storage and buffering.